Optimaalinen eläinsuojelu rikosprosessissa ja julkishallinnossa - Koskela, Tarja (Publications of the University of Eastern Finland, ISSN 1798-5757, 2017)
Optimal protection of animals in the criminal procedure and the public administration.
Keywords: eläinsuojelu; rikosprosessi; hallintolainkäyttö